Pengaruh Modifikasi Latihan Passing dengan Mengunakan Cone dalam Peningkatan Keterampilan Mengolah Bola SSB Sinar Muda Mappedeceng - Yodi, Yodi; Pajarianto, Hadi; Kahar, Irsan (Universitas Hamzanwadi, 2025)
This study aims to determine the effect of modifying passing training using cones in improving the skills of managing SBB Sinar Muda Mappadeceng bolas. The research method used is experimental. The population in this study was 55 people with a sample size of 20 people. Data collected from pretest and posttest, data management using IBM SPSS Statistic 22 software. The results showed that the normality test with Shapiro-Wilk can be known that this data is normally distributed because the posttest value (933) > from 0.05, so the data is normally distributed. Furthermore, the results of the homogeneity test can be seen that sig. is .168, because the value of .168 > 0.05 it can be concluded that the data variance is homogeneous. Finally, the hypothesis test shows the Asymp.Sig (2-tailed) t value (0.000 < 0.05). students in the good enough category only numbered 4 students (20%), 6 students (30%) were sufficient, and 10 students (50%) were not good enough. Whereas in the posttest students in the very good category amounted to 3 students (15%), 10 students (50%) were good, and 7 students (35%) were quite good. So it can be said that the modification of passing training using cones has an effect in improving the skills of managing the ball SSB Sinar Muda Mappadeceng.